The conformity of test construction of the achievement test papers of college teachers a case study - dela Rama, Pablito A. (Siliman Journal, 2011)
This paper examines the rules in test construction that are commonly observed and violated by the college teachers of Siliman University and measures if significant relationship exists between the profile teachers - sex, number of years in teaching, number of education units taken, number of seminars in test construction attended, and academic background - and their ability to observe the rules of test construction. Although majority of the rules of the five types of tests investigated were observed by teachers, particularly the True or False type, there are still rules where violations were greater than compliance, particularly in the Matching and Enumeration types. Moreover, the sex of teachers and number of seminars in test construction attended by these teachers are significantly related to their adherence to the rules of test construction. Therefore, more credits or time to courses in teacher training and seminars in test construction among in-service teachers are recommended to address the need, particularly of male teachers, to enhance their skills in constructing quality test questions.